Pelatihan Edukasi Pemanfaatan Bahan Alam Untuk Pembuatan Produk Bioteknologi Bagi Ibu PKK Bina Mufakat - Elfrida Elfrida; Sukirno Sukirno; Nursamsu Nursamsu (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
The role of biotechnology is very rapid and broad in the aspect of fulfilling human needs, one of which is in the food industry. Biotechnology processes, both conventional and modern, cannot be separated from the role of microorganisms. Certain microorganisms are used in traditional food preparation through fermentation such as in the manufacture of yogurt, tape, cheese, soy sauce, yeast. Foods resulting from biotechnology that take advantage of the role of microorganisms and must pay attention to the critical point of halal. This needs to be considered so that each production process can be ensured to avoid contamination of non-halal materials. This product will later be used for Ms. PKK Bina Mufakat both for her own use and also as an entrepreneurial opportunity for the home industry. The problem of community service activities is that there is no group development in making biotechnology products, and there is no entrepreneurship development for PKK Bina Mufakat Gampong Bayeun. The method in service activities is a type of training method. The results of community service are the creation of a product that is useful and can be used as a home industry business opportunity.